2005
DOI: 10.2466/pms.101.5.90-94
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Directionality and Orientation in Drawings by Young Children and Adults

Abstract: The present study examined the relationship between directionality of drawing movements and the orientation of drawn products in right-handed adults and young children for 27 Japanese kindergartners and 29 Japanese university students who were asked to draw with each hand fishes in side view and circles from several starting points. Significant values of chi2 for distributions of frequencies of orientation of the fish drawings and the direction of circular drawing movement indicated that adult right-handers dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…Reading/writing direction affected performance when the dominant hand was used but not when the nondominant hand was used to draw. A similar finding of lack of a consistent directional effect with the nondominant hand regardless of reading/writing direction was noted by Taguchi and Noma (2005) and Kebbe and Vinter (2013), who attributed it to motor facilitation in executing outward movements, determined by musculoskeletal organization (see Vaid, 2011).…”
Section: Role Of Hand Dominancesupporting
confidence: 62%
See 2 more Smart Citations
“…Reading/writing direction affected performance when the dominant hand was used but not when the nondominant hand was used to draw. A similar finding of lack of a consistent directional effect with the nondominant hand regardless of reading/writing direction was noted by Taguchi and Noma (2005) and Kebbe and Vinter (2013), who attributed it to motor facilitation in executing outward movements, determined by musculoskeletal organization (see Vaid, 2011).…”
Section: Role Of Hand Dominancesupporting
confidence: 62%
“…This Spatial Handedness and Reading/Writing Embodiment effect (or SHARE) is especially evident when using the dominant hand. Differences in graphic production behavior when using the dominant versus nondominant hand have been previously noted (e.g., Taguchi & Noma, 2005;Taguchi, 2010). Motor training and experience can modify handedness biases (Suitner, Maass, Bettinsoli, Carraro, & Kumar, 2017), and possibly affect brain areas associated with the primary motor cortex (Sanes & Donoghue, 2000).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Recently, researchers have reported effects of reading and writing habits on cognitive performances such as information processing, spatial cognition, aesthetic preference, and so on (e.g., Chokron & De Agostini, 2000;Dobel, Diesendruck, & Bölte, 2007;Rayner, Li, Williams, Cave, & Well, 2007). Some researchers have suggested that reading and writing habits may influence fine motor skills such as writing and drawing movements (e.g., Vaid, Maharaj, Sakhuja, & Gupta, 2002;Fagard & Dahmen, 2003;Taguchi & Noma, 2005). Vaid, et al (2002) asked native readers of Hindi (a language read and written from left to right) and Urdu (a language read and written from right to left), ages 15 to 20 years, to draw five objects such as an arrow or a pencil, with the dominant hand, and observed the direction of the stroke employed in drawing.…”
mentioning
confidence: 99%
“…Analysis showed that 85% of 100 figures produced by 20 right-handed Hindi readers were drawn from left to right while 67% of 100 figures produced by 20 right-handed Urdu readers were drawn from right to left. Taguchi and Noma (2005) reported that Japanese righthanded adults tended to draw a circle clockwise with the dominant hand, whereas Fagard and Dahmen (2003) stated that their right-handed French participants, ages 7 to 9 years, drew a circle counterclockwise. The directional bias of right-handed English schoolchildren and adults was also counterclockwise (Goodnow, Friedman, Bernbaum, & Lehman 1973;Van Sommer, 1984).…”
mentioning
confidence: 99%